Study on Chemical and Organoleptic properties Sale King Banana – Dried by Cabinat Drying - Masuku, Mustamian Anwar (Agrikan Jurnal Agribisnis Perikanan, 2021)
The aim of this study is sale to determine the good drying time of the chemical and organoleptic properties by using cabinet drying and the chemical and organoleptic properties of sale of plantain dried by cabinet drying. This research method used a simple one-factor completely randomized design (CRD) consisting of 10 treatments and 2 replications to obtain 10x2 = 20 experimental units. The data obtained were analyzed for variance, and if there was a significant effect, it was continued with the Least Significant Difference Test (LSD) at the significant level α 0.05. A good drying plant for sale is during cabinet drying for 26 hours, with a moisture content of 33.02% of sale plantain, an ash content of 3.05% and a sucrose content of 4.18%. Sale of plantain with cabinet drying resulted in moisture content ranging from 26.49-38.02%, ash content 3.05-4.35%, sucrose content 4.18% -5.21%, and organoleptics including color values ranging from 2.97-3.65%, aroma 3.40-4.12%, texture 2.87-4.00%, and taste 3.20-3.88%.